Synopsis: Prioritizing value chains for achieving Rwanda’s agrifood system transformation: A diagnostic of the agrifood system - Diao, Xinshen; Ellis, Mia; Rosenbach, Gracie; Mugabo, Serge; Pauw, Karl; Spielman, David J.; Thurlow, James (International Food Policy Research Institute, 2023)
Rwanda’s impressive economic growth over the past two decades has been accompanied by significant structural change in the broad economy and the agrifood system in particular. This note summarizes key results from a recent diagnostic of Rwanda’s agrifood system transformation, examining the effectiveness of productivity-led growth in different agricultural value chains for promoting development outcomes related to poverty, growth, employment, diet quality, and hunger. The findings show that value chains differ in their effectiveness in promoting these different development outcomes. The wheat and sorghum value chain, for example, has strong anti-poverty effects and is effective at reducing hunger, but is less effective at increasing jobs. Trade-offs will emerge as no single value chain is most effective at achieving every desired outcome; therefore, promoting a few value chains jointly will diversify agrifood system growth and help achieve multiple development outcomes simultaneously.